A (re) configuração dos sentidos do trabalho de jornalistas brasileiros nas plataformas de mídias sociais - Caporal, Gibsy Lisiê Soares (2024)
The Thesis explore the meanings revealed in a virtual world, where social networks have been incorporated by platforms, the offline world blends with the online world, and new dynamics of virtualized work begin to (re)configure for journalists. The research question is: How are the meanings of communication and work for journalists being (re)configured through social media platforms? The general objective of the study is to understand how the meanings of communication and work for journalists are being (re)configured through social media platforms. To this end, five specific objectives were structured, and a theoretical analysis was conducted, drawing on authors such as Couldry and Hepp (2017, 2020); Castells (2003, 2006); Levy (2010, 2011, 2015); Van Dijck, Poell, Wall (2018); Poell, Nieborg, Van Dijck (2019); Helmond (2015); Antunes (2020, 2021); Fígaro (2008, 2019, 2021); Grohmann (2020, 2021); Gorz (2005); and Standing (2020), who were brought into the discussion and helped to form a conceptual matrix supporting the research context. Methodologically, an exploratory, descriptive, and qualitative approach was followed, with the study corpus analyzing the work environment of journalists through an empirical set formed by interviews and a set of posts on X (Twitter) that reveal journalists' discourse about their work. We ultimately identified discursive fields where the meanings (re)shaping communication and work were recognized in the discursive formations: (1) Power in new spaces of dispute, (2) Journalists' work in the virtual domain, and (3) Affects on social media platforms. The discourse of journalists about their work shows that the meanings of communication and work are being (re)signified by journalists within this platformized ecosystem. Thus, the enunciated discourses create a mark of meanings that we call the Biometry of Journalism on Platforms. The thesis begins with an introduction, followed by chapters on Transformations of Journalism in Brazil, A Virtual and Platformized World, and Changes in the World of Work. It then presents Methodological Procedures, Journalists Speak (Data Interpretation Analysis), Conclusion, and References.